Perceptions of the Exemption Policy on Maternal Mothers Healthcare Service Delivery in Iringa Municipality, Tanzania (Tanzania Journal for Population studies and Development, 2022)
This article presents perceptions on the effect of the user-fees exemption policy on maternal mothers in Iringa Municipality, in Iringa, Tanzania. It specifically presents outcomes of the policy on healthcare services offered to maternal mothers. The study employed a cross-sectional research design, with a purposively selected sample of 74 respondents. Data was collected through questionnaires, in-depth interviews, and documentary review; and analysed descriptively and thematically. The results indicated that, on the one hand, the policy increased equal chances in accessing health services among maternal mothers; increased the number of deliveries in health facilities; reduced the number of maternal deaths and uncertainty of delivery for maternal mothers; and improved chances of survival and the overall health of maternal mothers and their babies. On the other hand, the policy tempted unlawful payments; increased household’s dependency on the government; increased municipal expenditure; led to the shortage of beds, drugs as well as skilled health workers; and invited indirect costs. Despite all these challenges, the exemption policy was important as access to health services for maternal mothers improved greatly. Based on the study results, it is recommended that unlawful payments should be controlled; municipal expenditure budget, hospital beds, drugs, and skilled health workers be increased; and indirect costs be minimized.